1993
DOI: 10.1007/bf01296107
|View full text |Cite
|
Sign up to set email alerts
|

Olsalazine in maintenance of clinical remission in patients with ulcerative colitis

Abstract: Frequent minor side effects are associated with sulfasalazine. The realization that it is the 5-aminosalicylic acid moiety that is the active component of sulfasalazine and that the side effects are probably due to the sulfapyridine has prompted the search for a similar but safer compound. Olsalazine, consisting of two molecules of 5-ASA without sulfasalazine may avoid the problems due to sulfasalazine. One hundred one patients were entered into a double-blind placebo-controlled study of the use of olsalazine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 20 publications
0
30
0
Order By: Relevance
“…Analysis of 14 trials of maintenance therapy with mesalazine of 1 year duration show great variability, with relapse rates from 23%–63% 1224. The mean relapse rate of these pooled trials (involving 1540 patients) was 42%.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of 14 trials of maintenance therapy with mesalazine of 1 year duration show great variability, with relapse rates from 23%–63% 1224. The mean relapse rate of these pooled trials (involving 1540 patients) was 42%.…”
Section: Methodsmentioning
confidence: 99%
“…We identified eight placebo-controlled trials of 5-ASA in maintenance of remission in ulcerative colitis, [22][23][24][25][26][27][28][29] including three using sulfasalazine (Table 3). Follow-up was between 6 months and 1 year.…”
Section: Corticosteroidsmentioning
confidence: 99%
“…Early randomized trials of olsalazine [96] and mesalamine [97] were disappointing, with mesalamine showing no benefit and olsalazine showing an increased incidence of diarrhea. The negative result for olsalazine was not surprising, because a similar increase in diarrhea prevalence was seen in IBD patients [98]. A study of balsalazide found that it did not significantly alleviate clinical symptoms [99].…”
Section: Radiotoxicity Prevention and Treatmentmentioning
confidence: 98%